Single-incision laparoscopic myomectomy: A review of the literature and available evidence - Naoyuki Yoshiki (Wolters Kluwer Medknow Publications, 2016)
Single-incision laparoscopic surgery (SILS) has become more feasible and safer for the patient by improvement in conventional laparoscopic techniques and availability of more advanced instruments. To date, there are many publications regarding having applied this technique to most benign gynecologic disorders. However, with regard to single-incision laparoscopic myomectomy, there are only a handful of publications. Researchers in the literature show that single-incision laparoscopic myomectomy is a safe and effective alternative to conventional laparoscopic myomectomy in a selected group of women. However, all researchers have emphasized the difficulty of intracorporeal suturing through a single port. In the future, a barbed suture and the use of a culdoscope may be useful to perform single-incision laparoscopic myomectomy. The integration of SILS and natural orifice transluminal endoscopic surgery will certainly contribute to a wider application of this approach.